2007
DOI: 10.1088/0957-4484/18/47/475103
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared laser-triggered carbon nanohorns for selective elimination of microbes

Abstract: Carbon nanomaterials, such as carbon nanohorns and carbon nanotubes, have attracted considerable attention for their biomedical applications. We report here the first application of carbon nanohorns (CNHs) as potent laser therapeutic agents for highly selective elimination of microorganisms. This is the first report, supported by direct observations, of the highly selective elimination of yeast and bacteria (Saccharomyces cerevisiae and Escherichia coli) by employing molecular recognition element–CNH complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
77
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 19 publications
3
77
0
Order By: Relevance
“…The UV-vis-NIR optical absorption spectrum of PBS dispersions of BSA-CNH peaked at 260 nm (Fig. 1B), characteristic of the absorption of tubular graphite and BSA molecules (27,28,44). The BSA-CNH complexes were ∼100-200 nm in diameter as estimated by atomic force microscopy and dynamic light scattering analyses (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The UV-vis-NIR optical absorption spectrum of PBS dispersions of BSA-CNH peaked at 260 nm (Fig. 1B), characteristic of the absorption of tubular graphite and BSA molecules (27,28,44). The BSA-CNH complexes were ∼100-200 nm in diameter as estimated by atomic force microscopy and dynamic light scattering analyses (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 93%
“…S1 A and B). An aqueous CNH complex dispersion (CNH concentration, 100 μg/mL) exhibited a significant increase in temperature over time (26)(27)(28) under 670-nm laser irradiation and with an increase in laser power, whereas control dispersions without CNH complexes showed no increase in temperature at all laser powers (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Recently, we [20,21] and other researchers [5,6] demonstrated that photoinduced nanocarbons, such as carbon nanohorns and CNTs, can operate as exothermic nanomaterials. We prepared an SWNT hybrid microchip to investigate the photoinduced exothermic properties of the PL-BSA-SWNT-PDMS composite (see Figure 3 a, b and the Supporting Information for details).…”
mentioning
confidence: 98%